An additional threat to ‘Cavendish’ banana growers and traders: The infection of banana peduncles by Fusarium oxysporum f. sp. cubense Tropical Race 4 (Foc TR4) - Bai, Tingting; Qin, Meng; Li, Xundong; Fan, Huacai; Xu, Shengtao; Zeng, Li; Zheng, Si-Jun (Scientific Societies, 2020)
Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4) is one of the most destructive banana pathogens worldwide. Until now, it has been generally accepted that Foc TR4 mainly colonizes the roots, rhizomes, pseudostems, and leaves of banana plants and spreads among plantations with infected planting material, soil residues, and water. Because banana Fusarium wilt is a typical vascular bundle disease, the pathogen is accepted to possess the ability to enter the peduncle. However, no scientific proof has been presented. Recently, more and more signs of peduncle Foc TR4 in ‘Cavendish’ plants in different banana production provinces of China suggest that further investigations ought to be made regarding fungal colonization. We observed discoloration inside some peduncles from the Foc TR4-infected plants. The fungus isolated from these symptoms was identified using Foc TR4-specific PCR, sequencing, and a host inoculation assay. In a greenhouse bioassay, the Foc TR4 isolates from the peduncle showed the capacity for reinfecting Brazilian plants (Cavendish, AAA) up into the leaves. Collectively, we isolated the Foc TR4 from the peduncle and directly testified that this pathogen can invade the peduncle via xylem vascular bundle.